EFEKTIVITAS KOMPOSISI PROBIOTIK YANG BERBEDA PADA TEKNOLOGI AKUAPONIK UNTUK MENGOPTIMALKAN LAJU PERTUMBUHAN DAN KONVERSI PAKAN IKAN GABUS (Channa sp.) - Fazril Saputra; Muhammad Agam Thahir; Mahendra Mahendra; Yusran Ibrahim; Muhammad Arif Nasution; Teuku Reza Efianda (JURNAL PERIKANAN TROPIS, 2020)
Snakehead (Channa sp.) was one of the superior freshwater fish species native to Indonesia that has been successfully domesticated. The increasing demand for snakehead fish on the market has resulted in the addition of cultivated land and water use. Aquaponics technology was a combination of fish farming and plants that grow without soil media. The aim of this research was to determine the best composition of probiotics that can be used in aquaponic technology to optimize growth rate and feed conversion of snakehead fish (Channa sp.). This research used an experimental method. The experimental design used was a completely randomized design with four probiotic combination treatments and each treatment was repeated three times. The results showed that awarding of different probiotic compositions in the aquaponic system resulted in a spesific growth rate that was not significantly (P>0.05) different between treatments. The highest value of spesific growth rate were in the treatment of probiotic composition of Lactobacillus casei and Saccharomyces cerevisiae with a value of 4.11%/ day. Awarding of different probiotic compositions in the aquaponic system results in significantly (P<0.05) different feed conversion ratio values. The best feed conversion ratio values were in the treatment of probiotic composition of Lactobacillus casei and Saccharomyces cerevisiae with a value of 1.78. The conclusion of this study was the composition of probiotic Lactobacillus casei and Saccharomyces cerevisiae was the best probiotic composition to increase the spesific growth rate and feed conversion ratio of snakehead fish.